2020
DOI: 10.1002/jnr.24651
|View full text |Cite
|
Sign up to set email alerts
|

Ciliary melanin‐concentrating hormone receptor 1 (MCHR1) is widely distributed in the murine CNS in a sex‐independent manner

Abstract: Melanin‐concentrating hormone (MCH) is a ubiquitous vertebrate neuropeptide predominantly synthesized by neurons of the diencephalon that can act through two G protein‐coupled receptors, called MCHR1 and MCHR2. The expression of Mchr1 has been investigated in both rats and mice, but its synthesis remains poorly described. After identifying an antibody that detects MCHR1 with high specificity, we employed immunohistochemistry to map the distribution of MCHR1 in the CNS of rats and mice. Multiple neurochemical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 125 publications
(209 reference statements)
6
35
0
Order By: Relevance
“…To assess the localization of mcherry MCHR1 during development and maturation of feeding behaviors, we also imaged brain sections from postnatal day 7 (P7), day 30 (P30), and adult mice ( Figure 3a and 3b ). mCherry MCHR1 localization is detected in neuronal cilia of both the ARC and PVN neurons at all ages as has been previously reported (Diniz et al, 2020). To confirm the reporter allele was also consistently observed in cilia that express endogenous MCHR1, we co-labeled ARC and PVN sections from Mchr1 +/ch mice with an MCHR1 antibody.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…To assess the localization of mcherry MCHR1 during development and maturation of feeding behaviors, we also imaged brain sections from postnatal day 7 (P7), day 30 (P30), and adult mice ( Figure 3a and 3b ). mCherry MCHR1 localization is detected in neuronal cilia of both the ARC and PVN neurons at all ages as has been previously reported (Diniz et al, 2020). To confirm the reporter allele was also consistently observed in cilia that express endogenous MCHR1, we co-labeled ARC and PVN sections from Mchr1 +/ch mice with an MCHR1 antibody.…”
Section: Resultssupporting
confidence: 85%
“…We then targeted cilia loss to GABAergic neurons using a Gad2 iresCre allele (Taniguchi et al, 2011; Ramos et al, 2021). We then assessed mCherry MCHR1 ciliary localization in the nucleus accumbens (NAc), where MCHR1 expression is abundant (Diniz et al, 2020; Ramos et al, 2021; Taniguchi et al, 2011). Heterozygous Gad2 iresCre : Ift88 +/F mice show robust mCherry MCHR1 and ADCY3 cilia co-localization ( Figure S2a ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemical analyses in brains of rats showed that ADCY3/MCHR1 double-positive neuronal primary cilia were localized in discrete regions including CPu and cerebral cortex [35]. Cilia MCHR1 merge with ADCY3 was also observed in cultured slices derived from the rat CPu and PFC (Fig.1 a,c).…”
Section: Resultsmentioning
confidence: 99%
“…The MCH-MCHR1 system constitutes a powerful regulatory system associated with food intake, energy expenditure, mood, and the sleep-wake cycle (38). Rodent MCHR1 is preferentially located in the primary cilia of neurons in the Accepted Article olfactory tubercle, hypothalamus, accumbens, and hippocampal formation, with MCHR1 in the latter concentrated in CA1 and CA3 regions but not in the dentate gyrus (42)(43)(44).We have previously described that MCH-MCHR1 binding mediates cilia length shortening in four different cultures of ciliated cells, including human retinal pigmented epithelial RPE1 cells (hRPE1) exogenously expressing MCHR1, rat hippocampal dissociated and slice neurons, and human-induced pluripotent stem cell-derived cortical neurons (44)(45)(46). We also demonstrated that Gi/o-dependent Akt phosphorylation is a major contributor of the initial stage of MCH-induced primary cilia shortening, leading to a downstream depolymerization of cytoplasmic tubulin and actin polymerization (44,45,47).…”
Section: Accepted Articlementioning
confidence: 99%